Keanekaragaman dan Kelimpahan Makrofauna Tanah pada Tiga Tegakan Berbeda di Hutan Pendidikan Gunung Walat - Cahyo Wibowo; Muhammad Fahmi Alby (Jurnal Silvikultur Tropika, 2020)
Soil macrofauna is an important factor in studying the biological soil quality. The activity of soil macrofauna affects the soil properties and condition. The objective of this study was to identify the soil macrofauna and analyze the diversity, evenness, and richness index of soil macrofauna on some sites at educational forest of gunung Walat. The macrofauna was collected using hand sorting method on 40x40 cm plots in 10 cm depth of soil and 3-5 cm thick of forest litters at Agathis, Pinus, and Puspa trees. The identification result showed that a total 641 individuals were found under Agathis, Pinus, and Puspa trees. The Pinus trees showed the highest frequency of soil macrofauna (377 individu). The Agathis trees showed the highest value of diversity index, that was H’=2.38, DMg=4.12, and E=0.78. Keywords: abundance, diversity, soil macrofauna, hand sorting method, Gunung Walat